Analisis Kekuatan Struktur Pondasi Mesin Induk di Bangunan Baru Kapal Tanker 6500 LTDW dengan Menggunakan Software Ansy - Wido Juni Wijanarko; Adi Wirawan Husodo; Eky Novianarenti (Proceedings Conference on Marine Engineering and its Application, 2020)
The strength construction to know the reaction that received in the construction to keep froma load, this aims to determine the safety and security of a construction. This research willfind equivalent stress value from a main engine foundation because loading from mainengine weight and main engine operation to customized with Class standard and to findsafety factor value. The load modelling will use Ansys Workbench 17.2, the method will useto analisys is a Finite Element metode to find stress value. This method will be used whendoing meshing in the Ansys Software. Meshing used size meshing 700 mm and fine for typemesh. The result have got the maximum stress value occurs at main engine Trial Conditionswith power at 100% got 237,8 MPa. Of All conditions analysis that have done have safetyfactor exceed than 1, maximum safety factor got 1,144 when main engine trial condition, sothis constructions confirmed safety construction. Then, maximum equivalent stress notpermitted exceed 264,37 MPa because it regulated from Class. Critical Area will receive inthe frame number 22.